Aurora kinase A is essential for correct chromosome segregation in mouse zygote - Kovarikova, Veronika; Burkus, Jan; Rehak, Pavol; Brzakova, Adela; Solc, Petr; Baran, Vladimir (Zygote (Cambridge, England), 2016)
Aurora-A kinase (AURKA), a member of the serine/threonine protein kinase family, is involved in multiple steps of mitotic progression. It regulates centrosome maturation, mitotic spindle formation, and cytokinesis. While studied extensively in somatic cells, little information is known about AURKA in the early cleavage mouse embryo with respect to acentrosomal spindle assembly. In vitro experiments in which AURKA was inactivated with specific inhibitor MLN8237 during the early stages of embryogenesis documented gradual arrest in the cleavage ability of the mouse embryo. In the AURKA-inhibited 1-cell embryos, spindle formation and anaphase onset were delayed and chromosome segregation was defective. AURKA inhibition increased apoptosis during early embryonic development. In conclusion these data suggest that AURKA is essential for the correct chromosome segregation in the first mitosis as a prerequisite for normal later development after first cleavage.
Keywords: Male; Time-Lapse Imaging; Embryo Culture Techniques; konfokální mikroskopie; MLN8237; fluorescenční mikroskopie; Aurora A; fosforylace; časosběrné zobrazování; zygota; Phosphorylation; Mitosis; myši inbrední BALB C; Pyrimidines; Spindle; mužské pohlaví; inhibitory proteinkinas; Mouse zygote; Mice, Inbred BALB C; Microscopy, Confocal; segregace chromozomů; Animals; Aurora kinasa A; kultivace embrya; Aurora Kinase A; ženské pohlaví; Microscopy, Fluorescence; pyrimidiny; zvířata; Azepines; Protein Kinase Inhibitors; myši inbrední C57BL; Mice, Inbred C57BL; mitóza; Chromosome Segregation; Zygote; Female; azepiny; Apoptosis